Detention in petty offense cases - Liżyńska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The right to freedom is one of the fundamental human rights. However, the said right to freedom, guaranteed by national and international laws, is subject to specific restrictions. One of the forms of restriction of human freedom is detention of a person suspected of having committed an offense applied in the law on petty offenses as a means of coercion. The legislator emphasizes that the application of this measure calls for compliance with basic principles — necessity and minimization, and the conditions for its use must be strictly fulfilled without the possibility to use the broad interpretation in this case.
Keywords: wolność; podstawowe prawa człowieka; przestępstwo; zatrzymanie; środki przymusu